The Impact of Shipping Connectivity on Environmental Quality, Financial Development, and Economic Growth in Regional Comprehensive Economic Partnership Countries - Bekteshi, Xhelil; Alshiqi, Sevdie; Jóźwik, Bartosz; Altin, Fatma Gul; Dogan, Mesut; Petrossyants, Tatyana (Journal of risk and financial management, 2024)
This study investigates the relationship between shipping connectivity, environmental quality, financial development, and economic growth among 14 countries in the Regional Comprehensive Economic Partnership (RCEP) from 2006 to 2019. Using panel-corrected standard error, Dynamic Seemingly Unrelated Regression, and Driscoll–Kraay estimation methods, the analysis reveals that shipping connectivity significantly contributes to financial development and economic growth, while also exerting a negative impact on environmental quality. These findings suggest that the maritime sector can have significant impacts not only on economic growth and financial development but also on environmental sustainability. In countries where maritime shipping has increased, particularly with the growth of trade, positive outcomes are observed in terms of financial development and economic growth, while negative impacts on environmental quality are also evident. This study provides insights for policymakers to develop strategies that maximize economic benefits while reducing environmental harm in order to achieve sustainable development in the maritime sector.